2016
DOI: 10.15252/embr.201540806
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of pattern recognition receptor signaling is mediated by a MAP kinase kinase kinase

Abstract: Pattern recognition receptors (PRRs) play a key role in plant and animal innate immunity. PRR binding of their cognate ligand triggers a signaling network and activates an immune response. Activation of PRR signaling must be controlled prior to ligand binding to prevent spurious signaling and immune activation. Flagellin perception in Arabidopsis through FLAGELLIN-SENSITIVE 2 (FLS2) induces the activation of mitogen-activated protein kinases (MAPKs) and immunity. However, the precise molecular mechanism that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 63 publications
1
43
0
Order By: Relevance
“…However, it is not clear how MAPKKK5 activates MPK4, which is known to be activated by MEKK1, MKK1, and MKK2. Another MAPKKK, MAPKKK7, has been shown to interact with FLS2 to negatively regulate flg22-triggered MPK activation, but the underlying mechanism remains unknown (Mithoe et al, 2016). Moreover, a bacterial protease called PrpL was shown to trigger MPK activation potentially through an unknown PRR (Cheng et al, 2015).…”
Section: A Number Of Rlcks Have Emerged As Central Components Linkingmentioning
confidence: 99%
“…However, it is not clear how MAPKKK5 activates MPK4, which is known to be activated by MEKK1, MKK1, and MKK2. Another MAPKKK, MAPKKK7, has been shown to interact with FLS2 to negatively regulate flg22-triggered MPK activation, but the underlying mechanism remains unknown (Mithoe et al, 2016). Moreover, a bacterial protease called PrpL was shown to trigger MPK activation potentially through an unknown PRR (Cheng et al, 2015).…”
Section: A Number Of Rlcks Have Emerged As Central Components Linkingmentioning
confidence: 99%
“…Interestingly, in contrast to the compromised MPK3/MPK6 activation triggered by chitin, the mapkkk5 mutant shows elevated MPK3/MPK6 activation stimulated by flg22, suggesting that MAPKKK5 inversely regulates chitin- and flg22-triggered signaling (162). In contrast, the MAPKKK MKKK7, associated with FLS2 and phosphorylated upon flg22 treatment, negatively regulates flg22-triggered MPK6 activation and the ROS burst through unknown mechanisms (113). …”
Section: Early Pattern Recognition Receptor Signaling Eventsmentioning
confidence: 99%
“…Recently, it was shown that FLS2-mediated PTI responses are also suppressed by the MAP kinase kinase kinase MKKK7, which interacts with FLS2 and is phosphorylated upon flg22 perception (Mithoe et al. 2016). …”
Section: Interference Of Type III Effectors With Basal Plant Defense mentioning
confidence: 99%